Using design theory to foster innovative cross-disciplinary research: Lessons learned from a research network focused on antimicrobial use and animal microbes' resistance to antimicrobials. (December 2018) - Vourc'h, Gwenaël; Brun, Juliette; Ducrot, Christian; Cosson, Jean-François; Le Masson, Pascal; Weil, Benoit
Abstract: Dealing with the major societal and research challenges related to antimicrobial use will require cross-disciplinary research and strong relationships between researchers and stakeholders. Design theories, such as the concept-knowledge (C-K) theory, can help spur the emergence of innovation. Here, our objective was to examine how the C-K theory could promote the development of novel, cross-disciplinary research projects on antimicrobial use and animal microbes' resistance to antimicrobials. A French research network (R2A2; Réseau Recherche Antibiotiques Animal) was created whose goal was to foster cross-disciplinary research and scientific discussion on these topics. The R2A2 network hosted general meetings and thematic workshops, during which participants brainstormed using C-K diagrams. The network's performance was evaluated through the evolution of C-K diagrams, project creation, and participant interviews. R2A2 led to the creation of a minimum of eight research projects. The participants felt network events facilitated interactions and collaborations with researchers in different disciplines. The R2A2 network has opened new avenues of research into several important topics: antimicrobial use on farms, the environmental impacts of antimicrobials, animal immunity, and alternative treatments. The keys to its success were: (i) participant interest; (ii) the use of C-K design theory to encourage cross-disciplinary thinking; (iii) the aim of fostering several small projects rather than one large project; and (iv) network responsiveness to participant needs with regards to meeting and workshop topics. C-K theory served a key role in promoting cross-disciplinary thinking on topics at the interface between research and stakeholder interests.